Inovasi Pengembangan Bahan Ajar Bahasa Arab Di Era Digital Pada SMA IT Al-Fityan School Gowa - Ummu Sulaimah Saleh; M Sholih Salimul Uqba; Nurlatipah; Slamet Daroini (Jurnal Pendidikan Bahasa Arab, 2023)
In facing the ever-evolving digital era, the development of Arabic teaching materials at Al-Fityan School Gowa IT High School requires innovations that are able to meet the needs of modern and effective learning. This article discusses various innovations applied in the development of Arabic teaching materials, ranging from the integration of multimedia technology to the utilization of interactive e-learning platforms. The main purpose of these innovations is to improve learning effectiveness, expand accessibility, and support students' various learning styles. Using qualitative research method through case study design, this article analyzes the implementation of digital technology in Arabic teaching materials at Al-Fityan School Gowa IT High School. Data were obtained through semi-structured in-depth interviews and analyzed with three stages of Miles and Huberman's qualitative data analysis technique: data reduction, data presentation and conclusion drawing. The results showed that the use of mobile applications, learning videos and other digital aids significantly increased students' interest and understanding of Arabic. The article also identifies challenges faced, including limited infrastructure and teacher readiness. Recommendations are given for the continued development of adaptive and inclusive digital teaching materials, in order to create a more dynamic and effective Arabic learning experience in this digital era.